Women and Men in Argentinean Political Tradition (1810–1947) - Hecht, Avital (Biografistyka Pedagogiczna, 2019)
María Estela Martínez de Perón, better known as Isabel Perón, became president of Argentina upon her husband’s death in 1974. She first served as vice president to her husband, Juan Domingo Perón, during his third term in office, starting in 1973. Compared to Peron, Argentina’s most legendary leader, serving from 1976 to 1974, Isabel (Peron’s third wife) possessed no evident leadership skills. Isabel significantly differed from Peron’s second wife, Eva (Evita) Perón, who was viewed as the ’sanctity’ in the eyes of its people. Eva served as a key partner in Peron’s rise to power during his first term in 1951-1946, accompanying him through his election campaign in which he was elected to a second term. Peron was overthrown from office in 1955 in a military coup. His second term began with an attempt to present the candidacy of Eva for vice president which proved unsuccessful as military chiefs, original partners of Peron, failed to support Eva’s candidacy. Very few women have been key players in Argentinian history. Change came about, however, during Peron’s first term, with support for women’s suffrage in 1947. With popular support ensuring the leader’s second term, this point in time changed the map on women’s rights. So while not considered a saint, such as Eva, Isabel may be analyzed as part of the personal and political life of Peron, as well as a key figure in Argentinian history.